The complete national geographic 108 years of natiopnal geographic on CD-ROM (National Geographic Society, 1997)
Every page, every issue ... Witness the destruction of the 1906 San Francisco earthquake through gripping eyewitness accounts. Join Commander Robert E. Peary in 1909 in his quest for the North Pole. Travel to Tibet with Sven Hedin, a bold adventurer who mapped 6,000 miles of the world's previously uncharted regions. And experience many more captivating moments from 1888-1909.